Shoulder range of motion and baseball arm injuries: A systematic review and meta-analysis - Bullock, G. S.; Faherty, M. S.; Ledbetter, L.; Thigpen, C. A.; Sell, T. C. (Journal of Athletic Training, 2018)
Objective Arm injuries in baseball players are a common problem. The identification of modifiable risk factors, including range of motion (ROM), is essential for injury prevention. The purpose of this review was to assess the methodologic quality and level of evidence in the literature and to investigate the relationship between shoulder ROM and the risk of arm injuries in baseball players.